Search for new long-lived particles at root s=13 TeV - KAYA, MİTHAT (My University, 2018)
A search for long-lived particles was performed with data corresponding to an integrated luminosity of 2.6 fb(-1) collected at a center-of-mass energy of 13 TeV by the CMS experiment in 2015. The analysis exploits two customized topological trigger algorithms, and uses the multiplicity of displaced jets to search for the presence of a signal decay occurring at distances between 1 and 1000 mm. The results can be interpreted in a variety of different models. For pair-produced long-lived particles decaying to two b quarks and two leptons with equal decay rates between lepton flavors, cross sections larger than 2.5 fb are excluded for proper decay lengths between 70-100 mm for a long-lived particle mass of 1130 GeV at 95% confidence. For a specific model of pair-produced, long-lived top squarks with R-parity violating decays to a b quark and a lepton, masses below 550-1130 GeV are excluded at 95% confidence for equal branching fractions between lepton flavors, depending on the squark decay length. This mass bound is the most stringent to date for top squark proper decay lengths greater than 3 mm. (C) 2018 The Author(s). Published by Elsevier B.V.
Keywords: Fizik; Astronomi ve Astrofizik; Temel Parçacıklar ve Alanlar; Temel Bilimler; Physics; Astronomy and Astrophysics; Basic Particles and Areas; Natural Sciences; ASTRONOMİ VE ASTROFİZİK; Uzay bilimi; Temel Bilimler (SCI); FİZİK, NÜKLEER; FİZİK, PARÇACIKLAR VE ALANLAR; ASTRONOMY & ASTROPHYSICS; SPACE SCIENCE; Natural Sciences (SCI); PHYSICS, NUCLEAR; PHYSICS; PHYSICS, PARTICLES & FIELDS; Nükleer ve Yüksek Enerji Fiziği; Fizik ve Astronomi (çeşitli); Genel Fizik ve Astronomi; Uzay ve Gezegen Bilimi; Fizik Bilimleri; Nuclear and High Energy Physics; Physics and Astronomy (miscellaneous); General Physics and Astronomy; Space and Planetary Science; Physical Sciences; CMS; Long-lived particles; GLUINO PRODUCTION; SQUARK